2013
DOI: 10.3389/fneur.2013.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Markers of Inflammation in Traumatic Brain Injury

Abstract: Within minutes of a traumatic impact, a robust inflammatory response is elicited in the injured brain. The complexity of this post-traumatic squeal involves a cellular component, comprising the activation of resident glial cells, microglia, and astrocytes, and the infiltration of blood leukocytes. The second component regards the secretion immune mediators, which can be divided into the following sub-groups: the archetypal pro-inflammatory cytokines (Interleukin-1, Tumor Necrosis Factor, Interleukin-6), the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
508
2
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 595 publications
(546 citation statements)
references
References 248 publications
(348 reference statements)
16
508
2
20
Order By: Relevance
“…Neuroinflammation is a critical factor inducing neuropathogenesis following TBI. 12,13 This means that resolving neuroinflammation may prevent or reduce the incidence of CTE development after rmTBI. Endogenous cannabinoids display antioxidant, anti-inflammatory, and neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neuroinflammation is a critical factor inducing neuropathogenesis following TBI. 12,13 This means that resolving neuroinflammation may prevent or reduce the incidence of CTE development after rmTBI. Endogenous cannabinoids display antioxidant, anti-inflammatory, and neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 To determine whether proinflammatory cytokines are elevated and astroglial cells are activated in our animal model of rmCHI and whether these inflammatory responses can be suppressed by MAGL inactivation, we assessed messenger RNA expression of proinflammatory markers vimentin (Vim) and cytokines, including IL-1β, IL-6 and TNFα, in the ipsilateral brain using qPCR analysis 4 days after the first injury and glial reactivity 8 days after the first TBI. As seen in Figure 2A, Immunoreactivity of Iba1 (microglial marker) and (C) glial fibrillary acidic protein (GFAP) (astrocytic marker) in the ipsilateral cortex (CTX), hippocampal CA1, and dentate gyrus (DG) was determined using immunostaining analysis.…”
Section: Monoacylglycerol Lipase Inhibition Promotes Neurological Recmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential patterns of localization of TNF-a receptors in neuronal and glial cells, their state of activation and the downstream effectors are all thought to play an important role in determining whether TNF-a will exert a beneficial or harmful effect on the CNS. Additionally, TNF-a contributes to the tissue injury induced by neutrophils by directly activating them, as well as by increasing the expression of such molecules as E-selectin, which cause the activated neutrophils to adhere to the surface of the endothelial cells [24]. It has also been shown that the inhibition of neutrophil adhesion to the endothelial cell surface markedly reduces the severity of the CNS injury induced by compressive trauma.…”
Section: Immunologic Sequelaementioning
confidence: 98%